2020
DOI: 10.2116/analsci.20p069
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Cu Modified Cu and Nano-Cu Modified Graphite Electrodes for Chemical Oxygen Demand Sensors

Abstract: Nano-Cu modified Cu (nano-Cu/Cu) and nano-Cu modified graphite (nano-Cu/C) electrodes were prepared by depositing a thin layer of copper nanoparticles on a Cu wire or graphite electrode. Chronoamperometric and cyclic voltammetry techniques were applied to deposit the nanoparticles. The effects of Cu 2+ concentration, deposition time, number of scan cycles, and scan rate were studied to determine the optimum conditions of the experiment. The applications of both electrodes in the COD analysis were performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…in the comparison table show that our research has conducted a more comprehensive and complete study on COD determination using the prepared Ti/TiO 2 electrode, especially for the detection of single-component and multi-component solutions. Although Zhang et al and Diksy et al mentioned multi-component solutions in their work, they did not conduct in-depth research and discussion on different types and ratios of organic solutions (Zhang et al 2009;Diksy et al 2020). However, this part of the research is of great significance for an actual measurement.…”
Section: Cod Determination Of Multi-component Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…in the comparison table show that our research has conducted a more comprehensive and complete study on COD determination using the prepared Ti/TiO 2 electrode, especially for the detection of single-component and multi-component solutions. Although Zhang et al and Diksy et al mentioned multi-component solutions in their work, they did not conduct in-depth research and discussion on different types and ratios of organic solutions (Zhang et al 2009;Diksy et al 2020). However, this part of the research is of great significance for an actual measurement.…”
Section: Cod Determination Of Multi-component Solutionmentioning
confidence: 99%
“…In this work, a secondary anodic oxidation method was used to convert Ti electrodes into Ti/ TiO 2 nanotube array electrodes with a high-efficiency contact area and multiple active sites. The preparation method is simple and easy to achieve in a short time, without any complex procedures and expensive instruments, compared to the detection method of photoelectrocatalysis (Li et al 2006a(Li et al , 2006b(Li et al , 2007Zhang et al 2009), the instruments for preparation (Li et al 2006a(Li et al , 2006b(Li et al , 2007Zhang et al 2009;Ma et al 2011;Mo et al 2015;Kabir et al 2019;Diksy et al 2020), and the preparation time (Li et al 2006a(Li et al , 2006b(Li et al , 2007Zhang et al 2009;Ma et al 2011;Mo et al 2015;Abdel-Salam et al 2018;Carchi et al 2019;Diksy et al 2020). The effect of the types and ratios of the organics on COD measurement by the Ti/TiO 2 electrode method was studied and discussed in the range of 5-150 mg/L COD.…”
Section: Cod Determination Of Multi-component Solutionmentioning
confidence: 99%
“…Analysis techniques that have been widely used usually utilize optical methods such as chemiluminescence, colorimetry, and fluorescence as well as conventional methods such as using high‐performance liquid chromatography (HPLC) and enzyme‐linked immunosorbent assay (ELISA)⋅ [12–16] . Among those methods, electrochemistry is one of the most well‐known methods for a cheap and non‐time consuming sensor application [17–20] . Accordingly, electrode material selection as a counter or working electrode is one of the important things to be considered in electrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Among those methods, electrochemistry is one of the most well-known methods for a cheap and non-time consuming sensor application. [17][18][19][20] Accordingly, electrode material selection as a counter or working electrode is one of the important things to be considered in electrochemistry. Working potential window, interaction between working electrode and modifier, medium, or electrochemical substrate, as well as stability and selectivity, are among the criteria that are usually considered in determining the appropriate electrode for an experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Many types of research on the detection of LEV have been reported by using various electrodes such as carbon nanotubes [11], nickel oxide porous films [12], modified screen-printed electrode (SPE) [13], and modified glassy carbon electrode (GCE) [14]. Among those electrodes, boron-doped diamond (BDD) electrode is famous for its excellent properties for sensor applications such as detecting arsenic (III) [15], neuraminidase [16], chemical oxygen demand (COD) [17], glucose [18], and many more applications such as for CO 2 reduction [19][20] and synthesis application [21]. This wide range of BDD sensor applications is known due to its low background current that supports the analysis in a very low concentration, wide potential window in aqueous solution, and high physical and chemical stability suitable for real applications [22][23].…”
Section: ■ Introductionmentioning
confidence: 99%